Sound design: an applied, experimental framework to study the perception of everyday sounds. Issue 2 (September 2014) - Susini, Patrick; Houix, Olivier; Misdariis, Nicolas
<x xml:space="preserve">Abstract</x> Mutations in late 20th-century sound design have transformed it from an empirical know-how into a full-fledged research field, with applications in the domain of everyday sound perception. This evolution leads us to propose an updated definition and a new description of the sound design process. Our updated definition, namely 'making intentions audible', is based on two types of intentions, one, essential, of function, and the other of form. We describe here three types of intentions of function, able to communicate information through an artifact. We then give a new description of the overall sound design process, as a combination of three steps (analysing, creating and testing), which articulate sound perception and sound design. Our first claim here is that the sound design process should be informed by knowledge, research and exploration of everyday sound perception; several industrial examples thereof will be presented. Our second claim is that sound design should be used to inform everyday sound perception research, both by suggesting new informative experiments and raising new methodological issues, ranging from sound design tools to experimental setups that need to be implemented specifically in the framework of sonic interaction design.